Strengthening Early Childhood Mathematics Education with Effective Math Teachers - ONOSHAKPOKAIYE, ODIRI E (The University of Kuningan, 2024)
The effective learning and instruction of early math is a top priority in every country's system of education. Math is first introduced to young children in a structured educational setting in their early years. It is crucial to take precautions of this crucial phase in order to support and build a strong, firm foundation throughout their math learning as well as other subjects. Throughout this era of life, children may develop mathematical concepts and skills for use in the future and scholastic success. Everybody has to be proficient in math since it is so important to our everyday life. To teach math effectively, teachers must be efficient in the subject. One prerequisite for this effective math education was the creation of an appropriate atmosphere for learning in the school setting. The classroom should be a comfortable place to study. By analyzing effective mathematics teaching, the study aimed to raise students' interest in and comprehension of mathematics. A review of certain research was conducted about the efficacy of arithmetic training. The study examines innovative math teachers and different strategies for stimulating students' interest in arithmetic through effective teaching techniques.